The escalation dating abuse workshop for college students: Results of an efficacy RCT. Issue 6 (18th August 2018) - Rothman, Emily F.; Paruk, Jennifer; Banyard, Victoria
ABSTRACT: Objective : Assess the efficacy of a college dating abuse (DA) prevention workshop.Participants : 85 students from Greek organizations.Methods : Two fraternities and two sororities were randomized to intervention or waitlist control. Participants completed a baseline and 3-month follow-up survey. Data were analyzed using MANOVA.Results : As compared to those in the control group, students assigned to the DA workshop felt more prepared to act as bystanders at follow-up and were more convinced that DA was a problem on campus. Those who saw the workshop also recognized more opportunities when they could intervene as bystanders with friends and strangers at follow-up than did controls.Conclusions : The DA workshop appears to have influenced students in the desired way, although not substantially. It is likely that a longer follow-up period and larger sample would reveal more meaningful changes from pre- to post-test.